A landscape approach to the surface archaeology of the Bos River, Tankwa Karoo, Northern Cape - Shaw, Matthew (Department of Archaeology, 2018)
Much of our current understanding of prehistoric human behavioural patterns during the Stone Age, is derived particularly from a robust set of chronological and technological sequences from caves and rock shelters, with some focus on open-air sites. The information gained from shelters cannot be ignored or downplayed, however, they offer a spatially and temporally limited view of prehistoric lifeways. The aim of this thesis is to provide an understanding of landscape use during the Stone Ages along the Bos River in the Tankwa Karoo, Northern Cape. Surveys were carried out around the Bos River, with the intention of mapping out and analysing all the surface stone artefacts. Analysing at the scale of the individual artefact, particularly temporally iconic artefacts, permits the landscape, although geologically and ecologically variable, to be viewed as a continuous space. The benefit of this approach allows for all artefacts across all types of settings to be analysed, providing a spatially subjective distribution of artefacts across the landscape. The evidence described in this thesis demonstrates an episodic occupation of the Tankwa Karoo during periods of increased resources, particularly the availability of food. The Bos River is a low-energy river that receives little rain and does not facilitate the formation of large rounded cobbles and boulders, explaining the lack of an occupation during the Earlier Stone Age (ESA), whereas an expedient organisation of locally sourced raw materials for stone tools characterise the Middle Stone Age (MSA) and Later Stone Age (LSA) periods in the Tankwa Karoo.